CONSTRUCTING PLURALISM THROUGH MEDIATIZATION: A CONTENT ANALYSIS OF MUHAMMADIYAH’S DIGITAL RELIGIOUS AUTHORITY AND IDENTITY - Fathurrahman Kamal; Surwandono Surwandono (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2026)
This study examines Muhammadiyah’s social construction of pluralism through the lens of mediatization theory as developed by Stig Hjarvard. It explores how a modern Islamic organization constructs, negotiates, and sustains religious authority in a rapidly changing public sphere through the systematic production and circulation of religious messages. The study employs qualitative content analysis to examine the construction of pluralism-related messages published on Muhammadiyah’s official website, muhammadiyah.or.id, during the period 2020–2025. The analysis is guided by the Pluralism Agenda-Setting Cluster, which assesses the frequency of news coverage, thematic dimensions, key figures, institutional forums, and discursive objectives embedded in Muhammadiyah’s public communication. The findings reveal that Muhammadiyah’s mediatized discourse on pluralism is not incidental but systematically organized. Its official media platform enables the organization to articulate pluralism productively, consolidate religious authority, and maintain its relevance as a visionary Islamic movement within Indonesia’s plural society. The study concludes that Muhammadiyah’s media platforms and official decrees function as plausibility structures: institutional supports that make a progressive and pluralistic Islamic reality credible, acceptable, and internally meaningful for its members. Through this process, Muhammadiyah performs strategic reality maintenance by anchoring a reformist Islamic identity, strengthening pluralistic commitments, and protecting its community from ideological instability.